Communication over medium-voltage distribution lines with inter-section crosstalk modeling - Vodrazka, Jiri; Hrad, Jaromir (2016 17th International Conference on Mechatronics - Mechatronika (ME), 2016)
The paper is focused on communication signal transmission over specific topology of medium-voltage overhead power distribution lines with crosstalk between different power sections. The following parameters have been measured and modeled: channel frequency response, interference, background noise. On this basis we have set up models and computed the estimated data throughputs for narrowband Power Line Communication technology using Orthogonal Frequency Division Multiplex modulation. High intensity of crosstalk can be advantageously used for transmitting of telecommunication signals between the different sections of the network; on the other hand, it is limited to the coexistence of separate communications networks, which mutually interfere, and thus the achievable transmission capacity is dramatically restricted.